Avaliação de pastas e argamassas geopoliméricas porosas obtidas a partir da incorporação de espuma pré-formada - Soares, Gustavo de Albuquerque (Universidade Federal de São Carlos, 2024)
The development of sustainable materials has been the subject of various studies in a broad technological context. In this regard, geopolymers are identified as potential binders for various applications, including acting as an alternative to Portland cement. This study investigated the production and properties of porous geopolymeric pastes and mortars, prepared from a mixture of metakaolin with an alkaline solution containing nano-silica and NaOH. Approximately 0.45 wt.% of xanthan gum was added to the water and foaming agent solution during foam preparation to enable the formation of stable and small bubbles, which are fundamental for the preparation of homogeneous porous geopolymers with uniform pores. The incorporation of 5 wt.% to 10 wt.% of pre-formed foam into the produced pastes resulted in the creation of specimens with low density, high porosity, low modulus of elasticity and reduced mechanical strength. In general, the pastes exhibited average pore diameters between 99 and 137 µm and high air permeability due to the interconnectivity of the present pores. For the porous mortars, compositions containing geopolymer or Portland cement as binders and different foam contents were evaluated. Samples with low density (1.18 to 2.11 g/cm³) and high porosity were obtained. Those containing geopolymer showed higher total porosity compared to cementitious ones. This characteristic resulted in compositions with low stiffness and mechanical resistance, as well as low thermal conductivity (0.29-0.34 W/m.K). The results confirmed the feasibility of producing porous and homogeneous microstructures, highlighting the great potential of geopolymers to act as substitutes for Portland cement in lightweight mortar compositions.
Evaluation of porous geopolymeric pastes and mortars obtained from the incorporation of preformed foam
Keywords: Geopolímeros; Espuma pré-formada; Cerâmicas porosas; Condutividade térmica; Geopolymers; Preformed foam; Porous ceramics; Thermal conductivity; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS